Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal display element, and diamine

JP7632576B2Active Publication Date: 2025-02-19NISSAN CHEM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023203724
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2023-12-01
Publication Date
2025-02-19
Estimated Expiration
2040-03-11

Smart Images

  • Figure 0007632576000001
    Figure 0007632576000001
  • Figure 0007632576000002
    Figure 0007632576000002
  • Figure 0007632576000003
    Figure 0007632576000003
Patent Text Reader

Abstract

To provide a highly reliable liquid crystal alignment film which causes less residual images and minimizes bright spots even in the presence of physical friction, such as rubbing by a spacer, and to provide a liquid crystal aligning agent for producing the liquid crystal alignment film, and a liquid crystal display element equipped with the liquid crystal alignment film.SOLUTION: A liquid crystal aligning agent is provided, containing a polymer obtained from a diamine having a structure represented by a formula (1) below. A represents a hydrogen atom, alkyl group with 1 to 3 carbon atoms, benzyl group, p-methoxybenzyl group, alkoxy group with 1 to 3 carbon atoms, acetyl group, benzoyl group, t-butyloxycarbonyl group, 9-Fluorenylmethoxycarbonyl group or R1R2R3Si group, where R1, R2 and R3 each independently represent an alkyl group or a phenyl group having 1 to 3 carbon atoms.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymer for use in a liquid crystal display element, a liquid crystal aligning agent, a liquid crystal alignment film, and a liquid crystal display element, and a novel diamine for use therein. [Background technology]

[0002] Various driving methods have been developed for liquid crystal display elements, which differ in electrode structure, physical properties of the liquid crystal molecules used, manufacturing process, etc., and known liquid crystal display elements include the TN (twisted nematic) type, STN (super-twisted nematic) type, VA (vertical alignment) type, MVA (multi-domain vertical alignment) type, IPS (in-plane switching) type, FFS (fringe field switching) type, and PSA (polymer-sustained alignment) type. These liquid crystal display elements are provided with a liquid crystal alignment film to align the liquid crystal molecules. The material for the liquid crystal alignment film is generally a coating made of a polymer such as polyamic acid, polyimide, or polysiloxane, because these have various good properties such as heat resistance, mechanical strength, and affinity with liquid crystal.

[0003] In recent years, there has been an increasing demand for higher image quality in liquid crystal display elements. In particular, in the case of displays for medical equipment and liquid crystal televisions, the problem of so-called "image retention," in which an image remains after a long period of operation, has become a major issue, and there is a strong demand for reducing image retention. From the viewpoint of further improving the quality of liquid crystal display elements, it is desirable to obtain liquid crystal display elements that are less susceptible to image retention than ever before.

[0004] In view of such circumstances, liquid crystal alignment films and liquid crystal aligning agents that provide liquid crystal display elements excellent in reducing afterimages have been known (see, for example, Patent Documents 1, 2 and 3).

[0005] Furthermore, liquid crystal display elements for the above-mentioned applications are required to have properties that enable them to withstand long-term use in harsh environments. Patent Document 4 discloses that a liquid crystal alignment agent containing a specific compound can provide a liquid crystal alignment film with little decrease in voltage retention rate even after exposure to a backlight for a long period of time, thereby providing a highly reliable liquid crystal display element. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2016 / 063834 Brochure [Patent Document 2] International Publication No. 2015 / 060366 Brochure [Patent Document 3] JP 2018-054761 A [Patent Document 4] International Publication No. 2010 / 074269 Brochure Summary of the Invention [Problem to be solved by the invention]

[0007] Furthermore, as so-called touch panel type liquid crystal display elements have become widespread, users often apply strong pressure to the display elements with their fingers. When this happens, the spacers present inside the liquid crystal display element move within the liquid crystal display element and rub against the liquid crystal alignment film. The liquid crystal alignment film stressed by the spacers is unable to regulate the alignment of the liquid crystals, and this causes a problem in that, even when the liquid crystal display element is displaying, for example, black, light escapes from the periphery of the spacers, resulting in the display of bright spots.

[0008] The configurations of liquid crystal alignment agents proposed in the past could not necessarily achieve all of the above problems. The present invention has been made based on the above circumstances, and its object is to provide a highly reliable liquid crystal display element that generates little residual images and can minimize bright spots even when physical friction occurs, such as rubbing by a spacer. Another object is to provide a liquid crystal alignment film with high film strength suitable for such a liquid crystal display element, and a liquid crystal alignment agent therefor.

[0009] In addition, in order to expand the effective pixel area in recent liquid crystal display elements, there is a demand to make the so-called frame area, where pixels are not formed at the peripheral edge of the substrate, smaller and smaller. As the frame of the panel becomes narrower, the sealant used when bonding two substrates to produce a liquid crystal display element is applied to a polyimide liquid crystal alignment film. However, since there is no polar group on polyimide, covalent bonds are not formed between the sealant and the liquid crystal alignment film surface, resulting in insufficient adhesion between the substrates. Therefore, the challenge is to improve the adhesion (adhesion) between the polyimide liquid crystal alignment film and the sealant or substrate. [Means for solving the problem]

[0010] As a result of intensive research to solve the above problems, the present inventors have found that various properties can be improved simultaneously by introducing a specific structure into a polymer contained in a liquid crystal alignment agent, and have completed the present invention. The present invention is based on this finding and has the following gist. 1. A liquid crystal aligning agent containing a polymer obtained from a diamine having a structure represented by the following formula (1):

[0011] [ka] A represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a benzyl group, a p-methoxybenzyl group, an alkoxy group having 1 to 3 carbon atoms, an acetyl group, a benzoyl group, a t-butyloxycarbonyl group, a 9-fluorenylmethoxycarbonyl group, or an R1R2R3Si group, and R1, R2, and R3 each independently represent an alkyl group having 1 to 3 carbon atoms or a phenyl group. Effect of the Invention

[0012] The liquid crystal aligning agent of the present invention provides a liquid crystal display element that generates little residual images and can minimize bright spots even when physical friction occurs, such as rubbing with a spacer, and a liquid crystal alignment film that provides the same.

[0013] According to the liquid crystal alignment agent of the present invention, a liquid crystal alignment film having excellent adhesion to a sealant can be obtained. By using this liquid crystal alignment film, a liquid crystal display element having excellent adhesion between substrates and high resistance to impact can be obtained. Although the mechanism by which the adhesion to the sealant is improved is not necessarily clear, it is believed that the hydroxyl group or methoxyl group of the specific diamine, or the hydroxyl group generated by the elimination of the protective group by heating, is exposed on the surface of the liquid crystal alignment film, and the adhesion between the liquid crystal alignment film and the sealant is improved by the interaction between the hydroxyl group or methoxyl group of the specific diamine and the functional group in the sealant. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The liquid crystal aligning agent of the present invention is a liquid crystal aligning agent containing a polymer (hereinafter also referred to as a specific polymer) obtained from a diamine having a structure represented by the above formula (1). Each condition will be described in detail below.

[0015] <Diamines having specific structures> The polymer of the present invention is a polymer obtained from a diamine having the structure of the above formula (1). Specific examples of the diamine of the above formula (1) include, but are not limited to, the following. Among them, from the viewpoint of reducing accumulated charge, (1-1), (1-2) and (1-3) are particularly preferred.

[0016] [ka]

[0017] <Polymer> The polymer of the present invention is a polymer obtained by using the above diamine. Specific examples include polyamic acid, polyamic acid ester, polyimide, polyurea, polyamide, etc., but from the viewpoint of use as a liquid crystal alignment agent, it is more preferable to use at least one selected from a polyimide precursor containing a structural unit represented by the following formula (6) and a polyimide which is an imidized product thereof.

[0018] [ka] In the above formula (6), X1 is a tetravalent organic group derived from a tetracarboxylic acid derivative, Y1 is a divalent organic group derived from a diamine containing the structure of formula (1), and R4 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. R4 is preferably a hydrogen atom, a methyl group, or an ethyl group from the viewpoint of ease of imidization by heating.

[0019] <<Tetracarboxylic acid dianhydride>> X1 is a tetravalent organic group derived from a tetracarboxylic acid derivative, and its structure is not particularly limited. X1 in the polyimide precursor is appropriately selected depending on the degree of required properties, such as the solubility of the polymer in a solvent, the applicability of the liquid crystal alignment agent, the alignment of the liquid crystal when made into a liquid crystal alignment film, the voltage holding ratio, the stored charge, etc., and one type of X1 may be present in the same polymer, or two or more types may be present in the same polymer. Specific examples of X1 include structures of formulas (X-1) to (X-46) shown in pages 13 and 14 of WO 2015 / 119168. Preferred structures of X1 are shown below, but the present invention is not limited to these.

[0020] [ka]

[0021] [ka] Of the above structures, (A-1) and (A-2) are particularly preferred from the viewpoint of photoalignment, (A-4) is particularly preferred from the viewpoint of further improving the relaxation speed of the accumulated charge, and (A-15) to (A-17) and the like are particularly preferred from the viewpoint of further improving the liquid crystal alignment and the relaxation speed of the accumulated charge.

[0022] <<Polymers (other structural units)>> The polyimide precursor containing the structural unit represented by formula (6) may contain at least one selected from the structural unit represented by formula (7) below and polyimide which is an imidized product thereof, within the range not impairing the effects of the present invention.

[0023] [ka] In formula (7), X2 is a tetravalent organic group derived from a tetracarboxylic acid derivative, Y2 is a divalent organic group derived from a diamine that does not contain the structure of formula (1) in the main chain direction, R5 is defined as R4 in formula (6), and R6 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. In addition, at least one of the two R6s is preferably a hydrogen atom.

[0024] Specific examples of X2 include the same structures as those exemplified for X1 in formula (6), including preferred examples. Y2 in the polyimide precursor is a divalent organic group derived from a diamine that does not contain the structure of formula (1) in the main chain direction, and its structure is not particularly limited. Y2 is appropriately selected depending on the degree of required properties, such as the solubility of the polymer in a solvent, the coatability of the liquid crystal alignment agent, the alignment of the liquid crystal when made into a liquid crystal alignment film, the voltage holding rate, and the accumulated charge, and may be one type in the same polymer, or two or more types may be mixed.

[0025] Specific examples of Y2 include the structure of formula (2) described in paragraph 4 of WO 2015 / 119168 and the structures of formulae (Y-1) to (Y-97) and (Y-101) to (Y-118) described in paragraphs 8 to 12 of WO 2015 / 119168; a divalent organic group having two amino groups removed from formula (2) described in paragraph 6 of WO 2013 / 008906; a divalent organic group obtained by removing two amino groups from formula (1) described in paragraph 8 of WO 2015 / 060360; a divalent organic group obtained by removing two amino groups from formula (1) described in paragraph 8 of JP 2012-173514; and a divalent organic group obtained by removing two amino groups from formulas (A) to (F) described in paragraph 9 of WO 2010-050523. Preferred structures of Y2 are shown below, but the present invention is not limited to these.

[0026] [ka]

[0027] [ka]

[0028] [ka]

[0029] [ka]

[0030] Of the above structures, (B-28) and (B-29) are particularly preferred from the viewpoint of further improving the film strength, (B-1) to (B-3) are particularly preferred from the viewpoint of further improving the liquid crystal alignment, (B-14) to (B-18) and (B-27) are particularly preferred from the viewpoint of further improving the relaxation rate of the accumulated charge, and (B-26) is preferred from the viewpoint of further improving the voltage holding ratio. When a polyimide precursor containing a structural unit represented by formula (6) also contains a structural unit represented by formula (7), the structural unit represented by formula (6) preferably accounts for 10 mol % or more, more preferably 15 mol % or more, and particularly preferably 20 mol % or more, of the total of formulas (6) and (7).

[0031] The molecular weight of the polyimide precursor used in the present invention is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and further preferably 10,000 to 100,000, in terms of weight average molecular weight.

[0032] The polyimide having the divalent group represented by formula (1) in the main chain may be a polyimide obtained by ring-closing the polyimide precursor. In this polyimide, the ring-closing rate of the amic acid group (also called the imidization rate) does not necessarily have to be 100% and can be adjusted as desired depending on the application or purpose. Methods for imidizing the polyimide precursor include thermal imidization, in which a solution of the polyimide precursor is heated as is, and catalytic imidization, in which a catalyst is added to a solution of the polyimide precursor.

[0033] The liquid crystal aligning agent of the present invention is a composition containing the above-mentioned specific polymer and an organic solvent, and may contain two or more specific polymers having different structures. In addition, the liquid crystal aligning agent of the present invention may contain a polymer other than the specific polymer (hereinafter also referred to as a second polymer) and various additives to the extent that the effects described in the present invention are achieved.

[0034] When the liquid crystal aligning agent of the present invention contains a second polymer, the ratio of the specific polymer to the total polymer components is preferably 5% by mass or more, and an example thereof is 5 to 95% by mass.

[0035] Examples of the second polymer include polyamic acid, polyimide, polyamic acid ester, polyester, polyamide, polyurea, polyorganosiloxane, cellulose derivatives, polyacetal, polystyrene or its derivatives, poly(styrene-phenylmaleimide) derivatives, and poly(meth)acrylates.

[0036] In particular, a polyamic acid obtained from a tetracarboxylic dianhydride component and a diamine component (hereinafter also referred to as a second polyamic acid) is preferable as the second polymer.

[0037] An example of a tetracarboxylic dianhydride component for obtaining the second polyamic acid is a compound represented by the following formula (11). The dianhydride component may be composed of one type of compound or two or more types of compounds.

[0038] [ka] In formula (11), A is a tetravalent organic group, preferably a tetravalent organic group having 4 to 30 carbon atoms.

[0039] Specific examples of A, including preferred examples, include the same structures as those exemplified for X1 in formula (6).

[0040] The diamine component for obtaining the second polyamic acid can be appropriately determined depending on the purpose, and for example, a diamine represented by the following formula (12) can be used.

[0041] [ka] (Y9 represents a divalent organic group. A9 each independently represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an alkynyl group having 2 to 5 carbon atoms, and may be the same or different. From the viewpoint of liquid crystal alignment, A9 is preferably a hydrogen atom or a methyl group.)

[0042] The structures of Y9 in formula (12), which are preferably used as the diamine component for obtaining the second polyamic acid, are shown below, but the present invention is not limited thereto.

[0043] [ka]

[0044] For the purpose of improving electrical properties and relaxation properties, Y9 is preferably a divalent organic group having a secondary or tertiary nitrogen atom, or a divalent organic group having -NH-CO-NH- in the molecule. Specific examples of formula (12) when Y9 is a divalent organic group having a secondary or tertiary nitrogen atom include diamines having a pyrrole structure described in International Publication WO2017 / 126627, preferably diamines having a structure represented by the following formula (pr):

[0045] [ka] (R 1 represents a hydrogen atom, a fluorine atom, a cyano group, a hydroxyl group, or a methyl group, and R 2 are each independently a single bond or a group "*1-R 3 -Ph-*2" and R 3 is a single bond, -O-, -COO-, -OCO-, -(CH2) l -, -O(CH2) m a divalent organic group selected from -O-, -CONH-, and -NHCO- (l and m represent integers of 1 to 5), *1 represents a site bonded to the benzene ring in formula (pr), *2 represents a site bonded to the amino group in formula (pr). Ph represents a phenylene group. n represents 1 to 3.), a diamine having a pyrrole structure described in International Publication WO2018 / 062197, preferably a diamine having a structure represented by the following formula (pn):

[0046] [ka] (R 1 and R 2each independently represents a hydrogen atom or a methyl group; R 3 is a single bond or a group "*1-R 4 -Ph-*2" and R 4 is a single bond, -O-, -COO-, -OCO-, -(CH2) l -, -O(CH2) m represents a divalent organic group selected from -O-, -CONH-, and -NHCO- (l and m represent integers of 1 to 5), *1 represents a site bonding to the benzene ring in formula (pn), *2 represents a site bonding to the amino group in formula (pn). Ph represents a phenylene group. n represents 1 to 3.), a diamine having a carbazole structure described in International Publication WO2018 / 110354, preferably a diamine having a structure represented by the following formula (cz):

[0047] [ka] (R 1 represents a hydrogen atom or a methyl group, R 2 represents a methyl group; diamines having a nitrogen-containing heterocycle described in paragraphs

[0173] to

[0188] of International Publication WO2015 / 046374 and diamines having a nitrogen-containing structure described in paragraph

[0050] of JP2016-218149A; diamines represented by the following formula (BP):

[0048] [ka] (X is a biphenyl skeleton or a fluorene ring; Y is a benzene ring, a biphenyl skeleton, or a group selected from -Ph-Z-Ph- (Ph is a phenylene group); Z is a divalent group represented by -O-, -NH-, -CH2-, -SO2-, -C(CH3)2-, or -C(CF3)2-; A and B are hydrogen atoms or methyl groups), 2,3-diaminopyridine, 2,6-diaminopyridine, 3,4-diaminopyridine, 2,4-Diaminopyrimidine, 5,6-diamino-2,3-dicyanopyrazine, 5,6-diamino-2,4-dihydroxypyrimidine, 2,4-diamino-6-dimethylamino-1,3,5-triazine, 1,4-bis(3-aminopropyl)piperazine, 4,4'-[4,4'-propane-1,3-diylbis(piperidine-1,4-diyl)]dianiline, 2,4-diamino-6-isopropoxy-1,3,5-triazine , 2,4-diamino-6-methoxy-1,3,5-triazine, 2,4-diamino-6-phenyl-1,3,5-triazine, 2,4-diamino-6-methyl-1,3,5-triazine, 2,4-diamino-1,3,5-triazine, 4,6-diamino-2-vinyl-1,3,5-triazine, 3,5-diamino-1,2,4-triazole, 6,9-diamino-2-ethoxyacridine lactate, 3,8-diamino-6-furan Examples of the diaminophenylamine include phenylphenanthridine, 1,4-diaminopiperazine, 3,6-diaminoacridine, bis(4-aminophenyl)-N-phenylamine, 4,4'-diaminodiphenyl-N-methylamine, 4,4'-diaminodiphenylamine, 3,6-diaminocarbazole, 9-methyl-3,6-diaminocarbazole, 9-ethyl-3,6-diaminocarbazole, and diamines represented by the following formulas (w1) to (w2).

[0049] [ka] (Sp represents phenylene, pyrrolidine, piperidine, piperazine, a divalent chain hydrocarbon group having 2 to 20 carbon atoms, or a group in which -CH2- of the divalent chain hydrocarbon group is substituted with a group selected from -O-, -CO-, -CO-O-, -NRCO- (R represents a hydrogen atom or a methyl group), -NRCOO- (R represents a hydrogen atom or a methyl group), -CONR- (R represents a hydrogen atom or a methyl group), -COS-, -NR- (R represents a methyl group), pyrrolidine, piperidine, and piperazine.)

[0050] Specific examples of the formula (12) when Y9 is a divalent organic group having -NH-CO-NH- in the molecule include diamines of the following formula (4) where A1 is -NH-CO-NH-, a group in which at least one -CH2- of an alkylene group having 2 to 20 carbon atoms is substituted with -NH-CO-NH-, or a group in which at least one -CH2- of an alkylene group having 2 to 20 carbon atoms is substituted with -NH-CO-NH- and at least one other -CH2- is substituted with a group selected from -O-, -CO-, -CO-O-, -NRCO- (R represents a hydrogen atom or a methyl group), -NRCOO- (R represents a hydrogen atom or a methyl group), -CONR- (R represents a hydrogen atom or a methyl group), -COS-, and -NR- (R represents a methyl group). More preferred specific examples of diamines include diamines represented by the following formulas (U-1) to (U-9).

[0051] [ka] (A1 represents a single bond, -NH-CO-NH-, or an alkylene group having 2 to 20 carbon atoms (wherein any -CH2- in the alkylene group may be substituted with -O-, -CO-, -CO-O-, -NRCO- (R represents a hydrogen atom or a methyl group), -NRCOO- (R represents a hydrogen atom or a methyl group), -CONR- (R represents a hydrogen atom or a methyl group), -COS-, -NR- (R represents a methyl group), or -NH-CO-NH-). A2 represents a halogen atom, a hydroxyl group, or an alkyl or alkoxy group having 1 to 5 carbon atoms (wherein any hydrogen atom in the alkyl or alkoxy group may be substituted with a halogen atom). a represents an integer of 0 to 4, and when a is 2 or more, A2 may be the same or different. b and c each independently represent an integer of 1 to 2.)

[0052] [ka]

[0053] Preferred specific examples of the diamines represented by the above formulas (w1) to (w2) include diamines represented by the following formulas (n3-1) to (n3-7) and diamines represented by the following formulas (n4-1) to (n4-6).

[0054] [ka]

[0055] [ka]

[0056] For the purpose of improving printability, diamine compounds having a carboxyl group (COOH group) or a hydroxyl group (OH group) can also be used. Specifically, 2,4-diaminophenol, 3,5-diaminophenol, 3,5-diaminobenzyl alcohol, 2,4-diaminobenzyl alcohol, 4,6-diaminoresorcinol, 2,4-diaminobenzoic acid, 2,5-diaminobenzoic acid, or 3,5-diaminobenzoic acid can be mentioned. Among them, 2,4-diaminobenzoic acid, 2,5-diaminobenzoic acid, or 3,5-diaminobenzoic acid is preferable. In addition, diamine compounds represented by the following formulas [3b-1] to [3b-4] and diamine compounds in which the amino group is a secondary amino group can also be used.

[0057] [ka] (In formula [3b-1], Q 1 represents a single bond, -CH2-, -C2H4-, -C(CH3)2-, -CF2-, -C(CF3)2-, -O-, -CO-, -NH-, -N(CH3)-, -CONH-, -NHCO-, -CH2O-, -OCH2-, -COO-, -OCO-, -CON(CH3)- or -N(CH3)CO-; m 1 and m 2 each independently represents an integer of 0 to 4, and m 1 +m 2 represents an integer of 1 to 4, and in formula [3b-2], m 3 and m 4 each independently represents an integer of 1 to 5; in formula [3b-3], Q 2 represents a linear or branched alkylene group having 1 to 5 carbon atoms; m 5 represents an integer of 1 to 5, and in formula [3b-4], Q 3 and Q 4 each independently represents a single bond, -CH2-, -C2H4-, -C(CH3)2-, -CF2-, -C(CF3)2-, -O-, -CO-, -NH-, -N(CH3)-, -CONH-, -NHCO-, -CH2O-, -OCH2-, -COO-, -OCO-, -CON(CH3)- or -N(CH3)CO-; m 6represents an integer from 1 to 4.)

[0058] As the diamine component for obtaining the second polyamic acid, in addition to the above, the diamine used in the specific polymer or a known diamine can be used, but the present invention is not limited thereto. The diamine component for obtaining the second polyamic acid may be one kind of diamine, or two or more kinds of diamines may be used in combination.

[0059] <Methods of producing polyamic acid, polyamic acid ester, and polyimide> The polyimide precursors, ie, polyamic acid ester, polyamic acid and polyimide, used in the present invention can be synthesized by known methods such as those described in International Publication WO2013 / 157586.

[0060] <Liquid crystal alignment agent> The liquid crystal alignment agent of the present invention contains a polymer (A). The liquid crystal alignment agent of the present invention may contain other polymers in addition to the polymer (A) and, if desired, a second polymer. Examples of the other polymers include polyamic acid, polyimide, polyamic acid ester, polyester, polyamide, polyurea, polyorganosiloxane, cellulose derivatives, polyacetal, polystyrene or its derivatives, poly(styrene-phenylmaleimide) derivatives, and poly(meth)acrylates.

[0061] The liquid crystal aligning agent is used to prepare a liquid crystal alignment film, and is preferably in the form of a coating liquid from the viewpoint of forming a uniform thin film. The liquid crystal aligning agent of the present invention is also preferably a coating liquid containing the above-mentioned polymer component and an organic solvent. In this case, the concentration of the polymer in the liquid crystal aligning agent can be appropriately changed depending on the thickness of the coating film to be formed. From the viewpoint of forming a uniform and defect-free coating film, it is preferably 1% by mass or more, and from the viewpoint of storage stability of the solution, it is preferably 10% by mass or less. A particularly preferred polymer concentration is 2 to 8% by mass.

[0062] The organic solvent contained in the liquid crystal alignment agent is not particularly limited as long as the polymer component is dissolved uniformly. Specific examples thereof include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethylsulfoxide, γ-butyrolactone, 1,3-dimethyl-2-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide (collectively referred to as "good solvents"). Among them, it is preferable to use N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, or γ-butyrolactone. The good solvent in the liquid crystal aligning agent of the present invention is preferably 20 to 99 mass %, more preferably 20 to 90 mass %, and particularly preferably 30 to 80 mass % of the total solvent contained in the liquid crystal aligning agent.

[0063] In addition, the organic solvent contained in the liquid crystal alignment agent is preferably a mixed solvent containing the above-mentioned solvent and a solvent (also called a poor solvent) that improves the coating property and the surface smoothness of the coating film when the liquid crystal alignment agent is applied. Specific examples of the organic solvent to be used in combination are listed below, but are not limited to these examples. For example, diisopropyl ether, diisobutyl ether, diisobutyl carbinol (2,6-dimethyl-4-heptanol), ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, 1,2-butoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, ethylene glycol monoacetate, ethylene glycol diacetate, propylene carbonate, ethylene carbonate, ethylene glycol monobutyl ether, ethylene glycol monoisoamyl ether, ethylene glycol monohexyl ether, propylene glycol monobutyl ether, 1-(2-butoxyethoxy)-2-propanol, 2-(2-butoxy)-2-propanol, Examples of the ethoxy)-1-propanol, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, propylene glycol diacetate, n-butyl acetate, propylene glycol monoethyl ether acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, propyl 3-methoxypropionate, butyl 3-methoxypropionate, n-butyl lactate, isoamyl lactate, diethylene glycol monoethyl ether, diisobutyl ketone (2,6-dimethyl-4-heptanone), and the like.

[0064] Of these, it is preferable to use diisobutyl carbinol, propylene glycol monobutyl ether, propylene glycol diacetate, diethylene glycol diethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol dimethyl ether, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monobutyl ether, ethylene glycol monobutyl ether acetate, and diisobutyl ketone.

[0065] Preferred combinations of good and poor solvents include N-methyl-2-pyrrolidone and ethylene glycol monobutyl ether, N-methyl-2-pyrrolidone, γ-butyrolactone and ethylene glycol monobutyl ether, N-methyl-2-pyrrolidone, γ-butyrolactone and propylene glycol monobutyl ether, N-ethyl-2-pyrrolidone and propylene glycol monobutyl ether, N-methyl-2-pyrrolidone, γ-butyrolactone, 4-hydroxy-4-methyl-2-pentanone and diethylene glycol diethyl ether, and N-methyl-2-pyrrolidone and γ-butyrolactone. Examples of poor solvents include propylene glycol monobutyl ether and 2,6-dimethyl-4-heptanone, N-methyl-2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether and diisopropyl ether, N-methyl-2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether and 2,6-dimethyl-4-heptanol, N-methyl-2-pyrrolidone, γ-butyrolactone and dipropylene glycol dimethyl ether, and N-methyl-2-pyrrolidone, propylene glycol monobutyl ether and dipropylene glycol dimethyl ether. These poor solvents are preferably 1 to 80% by mass, more preferably 10 to 80% by mass, and particularly preferably 20 to 70% by mass of the total solvent contained in the liquid crystal alignment agent. The type and content of such solvents are appropriately selected depending on the coating device, coating conditions, coating environment, etc. of the liquid crystal alignment agent.

[0066] The liquid crystal alignment agent of the present invention may additionally contain components other than the polymer component and the organic solvent. Such additional components include an adhesion assistant for increasing the adhesion between the liquid crystal alignment film and the substrate or between the liquid crystal alignment film and the sealant, a compound for increasing the strength of the liquid crystal alignment film (hereinafter also referred to as a crosslinking compound), a dielectric or conductive material for adjusting the dielectric constant or electrical resistance of the liquid crystal alignment film, etc.

[0067] As the crosslinkable compound, from the viewpoints of generating less AC afterimages and having a high effect of improving film strength, a compound having at least one group selected from the group consisting of an oxiranyl group, an oxetanyl group, a protected isocyanate group, a protected isothiocyanate group, a group containing an oxazoline ring structure, a group containing a Meldrum's acid structure, a cyclocarbonate group, and a group represented by the following formula (d), or a compound selected from compounds represented by the following formula (e) (hereinafter these are also collectively referred to as compound (C)).

[0068] [ka] (In the formula, R 71 is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or "-CH-OH", and R 72 and R 73 are each independently a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or "*-CH2-OH". * indicates a bond. A represents an organic group having a valence of (m+n) and an aromatic ring. m represents an integer of 1 to 6, and n represents an integer of 0 to 4.

[0069] Specific examples of compounds having an oxiranyl group include compounds having two or more oxiranyl groups, such as the compounds described in paragraph

[0037] of JP-A-10-338880 and compounds having a triazine ring skeleton described in International Publication WO2017 / 170483. Among these, compounds containing nitrogen atoms, such as N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, N,N,N',N'-tetraglycidyl-p-phenylenediamine, and compounds represented by the following formulas (r-1) to (r-3), are particularly preferred.

[0070] [ka]

[0071] Specific examples of the compound having an oxetanyl group include compounds having two or more oxetanyl groups described in paragraphs

[0170] to

[0175] of WO 2011 / 132751.

[0072] Specific examples of the compound having a protected isocyanate group include the compounds having two or more protected isocyanate groups described in paragraphs

[0046] to

[0047] of JP 2014-224978 A, and the compounds having three or more protected isocyanate groups described in paragraphs

[0119] to

[0120] of WO 2015 / 141598 A. Among these, the compounds represented by the following formulae (bi-1) to (bi-3) are preferred.

[0073] [ka]

[0074] Specific examples of compounds having a protected isothiocyanate group include compounds having two or more protected isothiocyanate groups, as described in JP-A-2016-200798.

[0075] Specific examples of the compound having a group containing an oxazoline ring structure include compounds containing two or more oxazoline structures, as described in paragraph

[0115] of JP-A-2007-286597.

[0076] Specific examples of the compound having a group containing a Meldrum's acid structure include compounds having two or more Meldrum's acid structures, as described in International Publication WO2012 / 091088.

[0077] Specific examples of the compound having a cyclocarbonate group include compounds described in International Publication WO2011 / 155577.

[0078] R of the group represented by formula (d) 71 , R 72 , R 73 Examples of the alkyl group having 1 to 3 carbon atoms include a methyl group, an ethyl group, and a propyl group.

[0079] Specific examples of the compound having a group represented by the formula (d) include compounds having two or more groups represented by the formula (d) described in International Publication WO2015 / 072554 and paragraph

[0058] of JP2016-118753A, compounds described in JP2016-200798A, etc. Among these, compounds represented by the following formulas (hd-1) to (hd-8) are preferred.

[0080] [ka]

[0081] Examples of the (m+n)-valent organic group having an aromatic ring in A of the formula (e) include an (m+n)-valent aromatic hydrocarbon group having 5 to 30 carbon atoms, an (m+n)-valent organic group to which an aromatic hydrocarbon group having 5 to 30 carbon atoms is bonded directly or via a linking group, and an (m+n)-valent group having an aromatic heterocycle. Examples of the aromatic hydrocarbon group include benzene and naphthalene. Examples of the aromatic heterocycle include a pyrrole ring, an imidazole ring, a pyrazole ring, a pyridine ring, a pyrimidine ring, a quinoline ring, an isoquinoline ring, a carbazole ring, a pyridazine ring, a pyrazine ring, a benzimidazole ring, a benzimidazole ring, an indole ring, a quinoxaline ring, and an acridine ring. Examples of the linking group include an alkylene group having 1 to 10 carbon atoms, a group obtained by removing one hydrogen atom from the alkylene group, and a divalent or trivalent cyclohexane ring. Any hydrogen atom of the alkylene group may be substituted with an organic group such as a fluorine atom or a trifluoromethyl group. Specific examples include compounds described in International Publication WO2010 / 074269. Preferred specific examples include the following formulae (e-1) to (e-9).

[0082] [ka]

[0083] The above compounds are examples of crosslinkable compounds, and are not limited thereto. For example, components other than those described above disclosed on pages 53

[0105] to 55

[0116] of International Publication No. 2015 / 060357 can be mentioned. In addition, the crosslinkable compound contained in the liquid crystal aligning agent of the present invention may be one type, or two or more types may be combined. The content of the crosslinkable compound in the liquid crystal aligning agent of the present invention is preferably 0.5 to 20 parts by mass relative to 100 parts by mass of the polymer component contained in the liquid crystal aligning agent, and more preferably 1 to 15 parts by mass from the viewpoints of proceeding with the crosslinking reaction to exhibit the intended effect and minimizing the occurrence of AC afterimages.

[0084] Examples of the adhesion aid include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldiethoxymethylsilane, 2-aminopropyltrimethoxysilane, 2-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltriethoxysilane, N-triethoxysilylpropyltriethylenetriamine, N-trimethoxy ... triethylenetriamine, 10-trimethoxysilyl-1,4,7-triazadecane, 10-triethoxysilyl-1,4,7-triazadecane, 9-trimethoxysilyl-3,6-diazanonyl acetate, 9-triethoxysilyl-3,6-diazanonyl acetate, N-benzyl-3-aminopropyltrimethoxysilane, N-benzyl-3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane, N-bis(oxyethylene)-3-aminopropyltrimethoxysilane, N-bis(oxyethylene)-3-aminopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,Examples of silane coupling agents include 4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, and 3-isocyanatepropyltriethoxysilane. When using these silane coupling agents, the amount is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, per 100 parts by mass of the polymer component contained in the liquid crystal alignment agent, from the viewpoint of reducing the occurrence of AC afterimages.

[0085] <Liquid crystal alignment film / Liquid crystal display element> A liquid crystal alignment film can be manufactured by using the liquid crystal alignment agent. The liquid crystal display element according to the present invention includes a liquid crystal alignment film formed by using the liquid crystal alignment agent. The operation mode of the liquid crystal display element according to the present invention is not particularly limited, and it can be applied to various operation modes such as TN (Twisted Nematic) type, STN type, vertical alignment type (including VA-MVA type, VA-PVA type, etc.), in-plane switching type (IPS type), FFS (Fringe Field Switching) type, and optical compensation bend type (OCB type).

[0086] The liquid crystal display element according to the present invention can be manufactured, for example, by the following steps (1-1) to (1-3). In step (1-1), different substrates are used depending on the desired operation mode. Steps (1-2) and (1-3) are common to each operation mode.

[0087] [Step (1-1): Formation of coating film] First, the liquid crystal aligning agent of the present invention is applied onto a substrate, and then the applied surface is heated to form a coating film on the substrate.

[0088] (1-1A) For example, when manufacturing a TN-type, STN-type or VA-type liquid crystal display element, first, two substrates each having a patterned transparent conductive film are used as a pair, and the liquid crystal alignment agent prepared above is applied to the transparent conductive film-formed surface of each substrate, preferably by offset printing, spin coating, roll coating or inkjet printing. As the substrate, for example, a transparent substrate made of glass such as float glass or soda glass; or a plastic such as polyethylene terephthalate, polybutylene terephthalate, polyethersulfone, polycarbonate or poly(alicyclic olefin) can be used. As the transparent conductive film provided on one side of the substrate, a NESA film (registered trademark of PPG, USA) made of tin oxide (SnO2), an ITO film made of indium oxide-tin oxide (In2O3-SnO2), or the like can be used. To obtain a patterned transparent conductive film, for example, a method of forming a pattern by photo-etching after forming a patternless transparent conductive film; a method of using a mask having a desired pattern when forming a transparent conductive film; or the like can be used. When applying the liquid crystal alignment agent, in order to further improve the adhesion between the substrate surface and the transparent conductive film and the coating film, the surface of the substrate on which the coating film is to be formed may be pretreated by applying a functional silane compound, a functional titanium compound, or the like.

[0089] After the liquid crystal alignment agent is applied, preheating (prebaking) is preferably performed for the purpose of preventing dripping of the applied liquid crystal alignment agent. The prebaking temperature is preferably 30 to 200°C, more preferably 40 to 150°C, and particularly preferably 40 to 100°C. The prebaking time is preferably 0.25 to 10 minutes, more preferably 0.5 to 5 minutes. Thereafter, the solvent is completely removed, and a baking (postbaking) step is performed for the purpose of thermally imidizing the amic acid structure present in the polymer as necessary. The baking temperature (postbaking temperature) at this time is preferably 80 to 300°C, more preferably 120 to 250°C. The postbaking time is preferably 5 to 200 minutes, more preferably 10 to 100 minutes. The film thickness of the film thus formed is preferably 0.001 to 1 μm, more preferably 0.005 to 0.5 μm.

[0090] (1-1B) When manufacturing an IPS or FFS type liquid crystal display element, a liquid crystal alignment agent is applied to the electrode forming surface of a substrate having an electrode made of a transparent conductive film or a metal film patterned into a comb-tooth shape and to one surface of an opposing substrate having no electrode, and then each applied surface is heated to form a coating film. The materials of the substrate and transparent conductive film used in this case, the coating method, the heating conditions after coating, the patterning method of the transparent conductive film or the metal film, the pretreatment of the substrate, and the preferred thickness of the coating film to be formed are the same as those in (1-1A) above. As the metal film, for example, a film made of a metal such as chromium can be used.

[0091] In both of the above (1-1A) and (1-1B), a liquid crystal alignment film or a coating film to be a liquid crystal alignment film is formed by applying the liquid crystal alignment agent onto a substrate and then removing the organic solvent. At this time, the coating film may be further heated after the coating film is formed to advance the dehydration ring-closing reaction of the polyamic acid, polyamic acid ester, and polyimide blended in the liquid crystal alignment agent according to the present invention, to form a more imidized coating film.

[0092] [Step (1-2): Treatment for imparting alignment ability] When manufacturing a TN-type, STN-type, IPS-type or FFS-type liquid crystal display element, a treatment is carried out to impart liquid crystal alignment ability to the coating film formed in the above step (1-1). This imparts the alignment ability of liquid crystal molecules to the coating film, forming a liquid crystal alignment film. Examples of the alignment ability imparting treatment include a rubbing treatment in which the coating film is rubbed in a certain direction with a roll wrapped with a cloth made of fibers such as nylon, rayon or cotton, and a photoalignment treatment in which the coating film is irradiated with polarized or non-polarized radiation. On the other hand, when manufacturing a VA-type liquid crystal display element, the coating film formed in the above step (1-1) can be used as it is as a liquid crystal alignment film, but the coating film may also be subjected to an alignment ability imparting treatment.

[0093] When the coating film is given liquid crystal alignment ability by photo-alignment treatment, ultraviolet light and visible light containing light with a wavelength of 150 to 800 nm can be used as radiation to be irradiated to the coating film. When the radiation is polarized, it may be linearly polarized or partially polarized. When the radiation used is linearly polarized or partially polarized, the radiation may be applied from a direction perpendicular to the substrate surface, from an oblique direction, or a combination of these. When applying non-polarized radiation, the radiation is applied in an oblique direction.

[0094] Examples of light sources that can be used include low-pressure mercury lamps, high-pressure mercury lamps, deuterium lamps, metal halide lamps, argon resonance lamps, xenon lamps, and excimer lasers. Ultraviolet rays in a preferred wavelength range can be obtained by using a light source in combination with, for example, a filter, a diffraction grating, and the like. The radiation dose is preferably 10 to 5,000 mJ / cm. 2 and more preferably 30 to 2,000 mJ / cm 2 It is.

[0095] The coating film may be irradiated with light while being heated in order to enhance reactivity. The temperature during heating is usually 30 to 250°C, preferably 40 to 200°C, and more preferably 50 to 150°C.

[0096] When ultraviolet light containing light having a wavelength of 150 to 800 nm is used, the light-irradiated film obtained in the above process can be used as a liquid crystal alignment film as it is, but the light-irradiated film may be baked, washed with water or an organic solvent, or a combination of these. The baking temperature is preferably 80 to 300°C, more preferably 80 to 250°C. The baking time is preferably 5 to 200 minutes, more preferably 10 to 100 minutes. The baking may be performed once or twice or more. The photo-alignment treatment here corresponds to a treatment of light irradiation in a state where the film is not in contact with the liquid crystal layer.

[0097] The organic solvent used for the washing is not particularly limited, but specific examples include water, methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, 1-methoxy-2-propanol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, methyl lactate, diacetone alcohol, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, propyl acetate, butyl acetate, and cyclohexyl acetate.

[0098] The liquid crystal alignment film after the rubbing treatment may be further subjected to a treatment to change the pretilt angle of a part of the liquid crystal alignment film by irradiating a part of the liquid crystal alignment film with ultraviolet light, or a treatment to form a resist film on a part of the surface of the liquid crystal alignment film and then perform a rubbing treatment in a direction different from that of the previous rubbing treatment, followed by removing the resist film, so that the liquid crystal alignment film has different liquid crystal alignment capabilities for each region. In this case, it is possible to improve the visibility characteristics of the resulting liquid crystal display element. The liquid crystal alignment film suitable for VA type liquid crystal display elements can also be suitably used for PSA (polymer sustained alignment) type liquid crystal display elements.

[0099] [Step (1-3): Construction of liquid crystal cell] (1-3A) Two substrates on which a liquid crystal alignment film is formed are prepared as described above, and a liquid crystal is disposed between the two substrates arranged opposite to each other to manufacture a liquid crystal cell. There are, for example, two methods for manufacturing a liquid crystal cell. The first method is a conventionally known method. First, two substrates are arranged opposite to each other with a gap (cell gap) between them so that the liquid crystal alignment films face each other, the peripheries of the two substrates are bonded together with a sealant, and liquid crystal is injected and filled into the substrate surfaces and the cell gap partitioned by the sealant, and then the injection hole is sealed to manufacture a liquid crystal cell. The second method is a technique called the ODF (One Drop Fill) method. For example, an ultraviolet light curable sealant is applied to a predetermined location on one of the two substrates on which a liquid crystal alignment film is formed, and liquid crystal is further dropped at several predetermined locations on the liquid crystal alignment film surface, and then the other substrate is bonded so that the liquid crystal alignment film faces each other, and the liquid crystal is spread over the entire surface of the substrate, and then ultraviolet light is irradiated over the entire surface of the substrate to cure the sealant, thereby manufacturing a liquid crystal cell. Regardless of which method is used, it is desirable to further heat the liquid crystal cell produced as described above to a temperature at which the liquid crystal used assumes an isotropic phase, and then slowly cool it to room temperature to remove the flow orientation that occurs during liquid crystal filling.

[0100] The sealing agent may be, for example, an epoxy resin containing a hardener and aluminum oxide spheres as spacers.

[0101] Examples of liquid crystals include nematic liquid crystals and smectic liquid crystals, among which nematic liquid crystals are preferred. For example, Schiff base liquid crystals, azoxy liquid crystals, biphenyl liquid crystals, phenylcyclohexane liquid crystals, ester liquid crystals, terphenyl liquid crystals, biphenylcyclohexane liquid crystals, pyrimidine liquid crystals, dioxane liquid crystals, bicyclooctane liquid crystals, cubane liquid crystals, etc. can be used. In addition, these liquid crystals may be used by adding cholesteric liquid crystals such as cholestyl chloride, cholesteryl nonaate, and cholesteryl carbonate; chiral agents such as those sold under the trade names "C-15" and "CB-15" (manufactured by Merck); and ferroelectric liquid crystals such as p-decyloxybenzylidene-p-amino-2-methylbutylcinnamate. The liquid crystal may also contain an anisotropic dye. The term "dye" may refer to a substance that can intensively absorb or transform light within at least a portion or the entire visible light range, for example, within the 400 nm to 700 nm wavelength range, and the term "anisotropic dye" may refer to a substance that can anisotropically absorb light within at least a portion or the entire visible light range. The color of the liquid crystal cell can be adjusted by using the dyes. The type of the anisotropic dye is not particularly limited, and for example, a black dye or a color dye can be used. The ratio of the anisotropic dye to the liquid crystal is appropriately selected within a range that does not impair the desired physical properties, and for example, the anisotropic dye can be included in a ratio of 0.01 to 5 parts by weight based on 100 parts by weight of the liquid crystal compound, but the ratio can be changed to an appropriate range as necessary.

[0102] (1-3B) When producing a PSA type liquid crystal display element, a liquid crystal cell is constructed in the same manner as in (1-3A) above, except that a photopolymerizable compound such as any of the following formulae (w-1) to (w-5) is injected or dropped together with the liquid crystal.

[0103] [ka]

[0104] Thereafter, the liquid crystal cell is irradiated with light while a voltage is applied between the conductive films of the pair of substrates. The voltage applied here can be, for example, 5 to 50 V DC or AC. The light to be irradiated can be, for example, ultraviolet light and visible light containing light with a wavelength of 150 to 800 nm, but ultraviolet light containing light with a wavelength of 300 to 400 nm is preferred. The light source for the irradiated light can be, for example, a low pressure mercury lamp, a high pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, or the like. The ultraviolet light in the above-mentioned preferred wavelength range can be obtained by using the light source in combination with, for example, a filter diffraction grating. The light irradiation dose is preferably 100 mJ / cm. 2 More than 30,000mJ / cm 2 More preferably, it is 100 to 20,000 mJ / cm 2 It is.

[0105] (1-3C) When a coating film is formed on a substrate using a liquid crystal alignment agent containing a compound (polymer or additive) having a photopolymerizable group, a liquid crystal cell may be constructed in the same manner as in (1-3A) above, and then a liquid crystal display element may be manufactured by a process of irradiating the liquid crystal cell with light while applying a voltage between the conductive films of a pair of substrates. According to this method, the advantages of the PSA mode can be realized with a small amount of light irradiation. The light irradiation to the liquid crystal cell may be performed in a state where the liquid crystal is driven by applying a voltage, or may be performed in a state where a low voltage is applied so that the liquid crystal is not driven. The voltage to be applied may be, for example, 0.1 to 30 V DC or AC. The explanation in (1-3B) above can be applied to the conditions of the light to be irradiated. The light irradiation treatment here corresponds to the light irradiation treatment in a state where the liquid crystal layer is in contact with the liquid crystal layer.

[0106] The liquid crystal display element according to the present invention can be obtained by attaching a polarizing plate to the outer surface of the liquid crystal cell. Examples of the polarizing plate to be attached to the outer surface of the liquid crystal cell include a polarizing film called an "H film" made by absorbing iodine while stretching and aligning polyvinyl alcohol, sandwiched between cellulose acetate protective films, and a polarizing plate made of the H film itself.

[0107] The liquid crystal display element according to the present invention can be effectively applied to various devices, and can be used in various display devices such as watches, portable games, word processors, notebook computers, car navigation systems, camcorders, PDAs, digital cameras, mobile phones, smartphones, various monitors, liquid crystal televisions, and information displays.

[0108] As described above, by using the liquid crystal aligning agent of the present invention, it is possible to obtain a liquid crystal alignment film which generates little residual images and can minimize bright spots even when physical friction occurs, such as rubbing with a spacer, and a liquid crystal display element having the same. In addition, the obtained liquid crystal display element has high reliability. EXAMPLES

[0109] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The abbreviations of the compounds used are as follows. (liquid crystal) MLC-3019 (Merck, positive type liquid crystal) (Diamine compounds) WA-1: A compound represented by the formula [WA-1] WA-2: A compound represented by the formula [WA-2]

[0110] [ka]

[0111] (Other diamine compounds) A1 to A7: Compounds represented by formulas [A1] to [A7], respectively

[0112] [ka] (Boc represents a tert-butoxycarbonyl group.)

[0113] (Acid dianhydride compound) B1 to B3: Compounds represented by formulas [B1] to [B3], respectively

[0114] [ka]

[0115] (solvent) NMP: N-methyl-2-pyrrolidone BCS: Ethylene glycol monobutyl ether GBL: γ-butyl lactone (Additives) S-1: 3-glycidoxypropyltriethoxysilane (Crosslinking agent) AD-1: A compound represented by the following formula (AD-1):

[0116] [ka]

[0117] (molecular weight measurement) The molecular weights of the polyimide precursor and polyimide were measured using a room temperature gel permeation chromatography (GPC) apparatus (GPC-101) (Showa Denko K.K.) and columns (KD-803, KD-805) (Shodex K.K.) as follows. Column temperature: 50℃ Eluent: N,N-dimethylformamide (additives: lithium bromide monohydrate (LiBr·H2O) 30 mmol / L, phosphoric acid anhydrous crystal (o-phosphoric acid) 30 mmol / L, tetrahydrofuran (THF) 10 mL / L) Flow rate: 1.0mL / min Standard samples for preparing a calibration curve: TSK standard polyethylene oxide (molecular weight: approximately 900,000, 150,000, 100,000, and 30,000) (manufactured by Tosoh Corporation) and polyethylene glycol (molecular weight: approximately 12,000, 4,000, and 1,000) (manufactured by Polymer Laboratory Co., Ltd.).

[0118] (Measurement of imidization rate of polyimide) 20 mg of polyimide powder was placed in an NMR (nuclear magnetic resonance) sample tube (NMR sampling tube standard, φ5 (Kusano Scientific Co., Ltd.)), deuterated dimethyl sulfoxide (DMSO-d6, 0.05 mass% TMS (tetramethylsilane) mixture) (0.53 mL) was added, and ultrasonic waves were applied to completely dissolve the powder. This solution was measured by 500 MHz proton NMR using an NMR measurement device (JNW-ECA500) (JEOL Datum Co., Ltd.). The imidization rate was calculated by the following formula using the proton peak integrated value of this proton and the proton peak integrated value of the proton peak derived from the NH group of the amic acid that appears around 9.5 to 10.0 ppm. Imidization rate (%) = (1-α·x / y) × 100 In the above formula, x is the integrated value of the proton peak derived from the NH group of the amic acid, y is the integrated value of the peak of the reference proton, and α is the ratio of the number of reference protons to one NH group proton of the amic acid in the case of polyamic acid (imidization rate 0%).

[0119] (viscosity measurement) In the Synthesis Examples and Comparative Synthesis Examples, the viscosity of the polyimide polymer was measured using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) with a sample amount of 1.1 mL, a cone rotor TE-1 (1°34', R24), and a temperature of 25°C.

[0120] (WA-1) was synthesized with reference to the following prior art: Salvatore Zarra, Jack K. Clegg, Jonathan R. Nitschke, Angewandte Chemie International Edition, 52, 18, (4837-4840, Supporting Information:S2-S3), (2013).

[0121] (WA-2) is a new compound that has not been published in the literature, and its synthesis is described in detail below.

[0122] The product described in Synthesis Example 1 below is 1 The product was identified by H-NMR analysis (analysis conditions are as follows). Equipment: BRUKER ADVANCE III-500MHz Measurement solvent: DMSO-d6 Reference material: Tetramethylsilane (TMS) (δ0.0 ppm for 1 H)

[0123] The abbreviations used in the present invention have the following meanings. THF: tetrahydrofuran DCE: 1,2-dichloroethane DMAP: N,N-dimethyl-4-aminopyridine

[0124] <<Monomer synthesis example 1: Synthesis of WA-2>>

[0125] [ka]

[0126] <Synthesis of compound [1]> In 1,2-dichloroethane (540 g), (4,4'-dinitro-[1,1'-biphenyl]-2,2'-diyl)dimethanol (60.0 g, 0.197 mol), triethylamine (45.9 g, 0.454 mol), and N,N-dimethyl-4-aminopyridine (2.39 g, 0.0197 mol) were charged and stirred under ice-cooling conditions. Di-tert-butyl dicarbonate (94.7 g, 0.434 mol) diluted with 1,2-dichloroethane (60 g) was added dropwise while paying attention to exotherm, and after the exotherm ceased, stirring was continued overnight at room temperature. After completion of the reaction, stirring was stopped, water (600 g) was added for liquid separation and washing, and liquid separation extraction was performed with chloroform (300 g × 2 times). The organic phase was concentrated, and the obtained crude product was purified by silica gel column chromatography using an ethyl acetate / hexane = 2 / 1 (volume ratio) mixed solvent, and the obtained solution was concentrated and dried to obtain a crude product of compound [1] (yield: 102 g). The obtained compound was used as it was in the next step. 1 1H-NMR (500 MHz) in DMSO-d6: 8.41 ppm (s, 2H), 8.33 ppm (d, 2H, J = 8.5 Hz), 7.58 ppm (d, 2H, J = 8.5 Hz), 4.90 ppm (s, 4H), 1.39 ppm (s, 18H).

[0127] <Synthesis of WA-2> In tetrahydrofuran (600 g), a crude product of compound [1] (101 g) and 3% platinum carbon (hydrous product) (8.00 g) were charged and stirred overnight at room temperature under a hydrogen atmosphere. After completion of the reaction, platinum carbon was removed by filtration and concentrated under reduced pressure. Methanol was added to the crude product and concentrated again and dried to obtain WA-2 (yield: 86.6 g, 0.195 mol). 1 1H-NMR (500 MHz) in DMSO-d6: 6.72 ppm (d, 2H, J = 8.0 Hz), 6.63 ppm (d, 2H, J = 2.5 Hz), 6.52 ppm (d, 1H, J = 2.5 Hz), 6.50 ppm (d, 1H, J = 2.0 Hz), 5.15 ppm (s, 4H), 4.64 - 4.59 ppm (m, 4H), 1.34 ppm (s, 18H).

[0128] (Synthesis Example 1) WA-1 (2.19 g, 9.00 mmol), A1 (1.83 g, 7.50 mmol), A2 (1.72 g, 7.50 mmol), A4 (2.04 g, 6.00 mmol) and B2 (1.12 g, 4.50 mmol) were mixed in NMP (50.6 g) and reacted at 50 ° C for 3 hours, after which B1 (5.32 g, 23.7 mmol) and NMP (30.1 g) were added and reacted at 40 ° C for 15 hours to obtain a polyamic acid solution [1] (viscosity 384 mPa s) with a resin solids concentration of 15 mass%. The obtained polyamic acid solution [1] (30.0 g) was diluted to 10.0 mass% with NMP, and then acetic anhydride (4.83 g) and pyridine (1.50 g) were added as imidization catalysts and reacted at 55°C for 2.5 hours. This reaction solution was poured into methanol (280 mL), and the resulting precipitate was filtered off. This precipitate was washed with methanol and dried under reduced pressure at 100°C to obtain polyimide powder (1). The imidization rate of this polyimide was 78.1%, the number average molecular weight was 12,322, and the weight average molecular weight was 44,438.

[0129] (Synthesis Example 2) WA-2 (4.00g, 9.00mmol), A1 (1.83g, 7.50mmol), A2 (1.72g, 7.50mmol), A4 (2.04g, 6.00mmol) and B2 (1.12g, 4.50mmol) were mixed in NMP (50.6g) and reacted at 50℃ for 3 hours, then B1 (5.32g, 23.7mmol) and NMP (30.1g) were added and reacted at 40℃ for 15 hours to obtain a polyamic acid solution [2] (viscosity 188mPa·s) with a resin solids concentration of 15% by mass. The obtained polyamic acid solution [2] (30.0 g) was diluted to 10.0 mass% with NMP, and then acetic anhydride (4.83 g) and pyridine (1.50 g) were added as imidization catalysts and reacted at 55°C for 2.5 hours. This reaction solution was poured into methanol (280 mL), and the resulting precipitate was filtered off. This precipitate was washed with methanol and dried under reduced pressure at 100°C to obtain polyimide powder (2). The imidization rate of this polyimide was 80.1%, the number average molecular weight was 10,582, and the weight average molecular weight was 41,856.

[0130] (Synthesis Example 3) A6 (1.19 g, 6.00 mmol), A7 (4.78 g, 24.0 mmol) and B2 (3.75 g, 15.0 mmol) were mixed in NMP (55.1 g) and reacted at 50°C for 3 hours. Then, B3 (4.06 g, 13.8 mmol) and NMP (23.0 g) were added and reacted at 70°C for 15 hours to obtain a polyamic acid solution [3] (viscosity 941 mPa s) with a resin solids concentration of 15% by mass. The number average molecular weight of the polyamic acid solution [3] was 15,244, and the weight average molecular weight was 40,724.

[0131] (Comparative Synthesis Example 1) A5 (1.91 g, 9.00 mmol), A1 (1.83 g, 7.50 mmol), A2 (1.72 g, 7.50 mmol), A4 (2.04 g, 6.00 mmol) and B2 (1.12 g, 4.50 mmol) were mixed in NMP (50.6 g) and reacted at 50°C for 3 hours, after which B1 (5.32 g, 23.7 mmol) and NMP (30.1 g) were added and reacted at 40°C for 15 hours to obtain a polyamic acid solution [R1] (viscosity 365 mPa s) with a resin solids concentration of 15% by mass. The obtained polyamic acid solution [R1] (30.0 g) was diluted to 10.0 mass% with NMP, and then acetic anhydride (4.83 g) and pyridine (1.50 g) were added as imidization catalysts and reacted at 55°C for 2.5 hours. This reaction solution was poured into methanol (280 mL), and the resulting precipitate was filtered off. This precipitate was washed with methanol and dried under reduced pressure at 100°C to obtain polyimide powder (R1). The imidization rate of this polyimide was 76.1%, the number average molecular weight was 10,958, and the weight average molecular weight was 39,958.

[0132] <Preparation of Liquid Crystal Alignment Agent> In the examples and comparative examples, preparation examples of liquid crystal alignment agents are described. Using the liquid crystal alignment agents obtained in the examples and comparative examples, liquid crystal display elements were produced and various evaluations were performed.

[0133] Example 1 NMP (22.0 g) was added to the polyimide powder (1) (3.00 g) obtained in Synthesis Example 1, and the mixture was stirred at 80 ° C for 15 hours to dissolve. To this solution (2.75 g), the polyamic acid solution [3] (3.30 g) obtained in Synthesis Example 3, NMP (1.35 g), GBL (3.675 g), BCS (3.00 g), AD-1 NMP 10 mass % diluted solution (0.248 g), and S-1 GBL 1 mass % diluted solution (0.825 g) were added, and the mixture was stirred at room temperature for 5 hours to obtain a liquid crystal alignment agent (V-1). No abnormalities such as turbidity or precipitation were observed in this liquid crystal alignment agent, and it was confirmed that it was a uniform solution.

[0134] Example 2 A liquid crystal alignment agent (V-2) was obtained in the same manner as in Example 1, except that the polyimide powder (1) was replaced with the polyimide powder (2) in Example 1. This liquid crystal alignment agent was confirmed to be a homogeneous solution without any abnormality such as turbidity or precipitation.

[0135] Comparative Example 1 A liquid crystal alignment agent (W-1) was obtained in the same manner as in Example 1, except that the polyimide powder (R1) was used instead of the polyimide powder (1) in Example 1. This liquid crystal alignment agent was confirmed to be a homogeneous solution without any abnormality such as turbidity or precipitation.

[0136] <Preparation of samples for evaluating seal adhesion> The samples for the adhesion evaluation were prepared as follows. The liquid crystal alignment agents (V-1) and (V-2) obtained in the examples and the liquid crystal alignment agent (W-1) obtained in the comparative example were applied to a 30 mm x 40 mm ITO substrate by spin coating. After drying for 120 seconds on a hot plate at 80°C, the substrate was baked for 20 minutes in a hot air circulation oven at 230°C to form a coating film with a thickness of 100 nm, thereby obtaining a substrate with a liquid crystal alignment film. The two substrates thus obtained were prepared, and a 4 μm diameter bead spacer was applied onto the liquid crystal alignment film surface of one of the substrates, after which a sealant (XN-1500T manufactured by Kyoritsu Chemical Industry Co., Ltd.) was dropped onto it. Next, the liquid crystal alignment film surface of the other substrate was placed inside, and the substrates were laminated together so that the overlap width around the substrates was 1 cm each. At that time, the amount of the sealant dropped was adjusted so that the diameter of the sealant after lamination was 3 mm. After fixing the two laminated substrates with clips, 3 J of 365 nm light was applied, and the substrates were thermally cured at 120°C for 1 hour to prepare a sample for adhesion evaluation.

[0137] <Evaluation of Adhesion> After that, the sample substrate obtained above was fixed at the edges of the top and bottom substrates with a Shimadzu Corporation bench-top precision universal testing machine AGS-X500N, and the force (N) required to peel the substrate was measured by pressing the substrate from the top center. A value of (N) less than 3.50 was defined as "bad" and a value of 3.50 or more was defined as "good". The results are shown in Table 1.

[0138] <Film strength (film hardness) evaluation> The liquid crystal alignment agent was applied by spin coating to the ITO surface of a glass substrate with an ITO electrode on the entire surface. After drying for 2 minutes on a hot plate at 80°C, a coating film with a thickness of 100 nm was formed. Polarized ultraviolet light was irradiated on the coating surface at 150 mJ / cm. 2The substrate was irradiated with light so that the alignment treatment was performed. The substrate was then baked at 230°C for 30 minutes in an IR oven to obtain a substrate with a liquid crystal alignment film. This liquid crystal alignment film was rubbed with a rayon cloth (roller diameter: 120 mm, roller rotation speed: 1000 rpm, moving speed: 20 mm / sec, indentation length: 0.6 mm). The substrate was measured using a HZ-V3 haze meter manufactured by Suga Test Instruments. A haze value of 0.3 or more was defined as "bad" and a value of less than 0.3 was defined as "good" for evaluation. The results are shown in Table 1.

[0139] <Preparation of liquid crystal cells for evaluating liquid crystal alignment> A method for preparing a liquid crystal cell for evaluating the liquid crystal alignment property will be described below. A liquid crystal cell having the configuration of a liquid crystal display element of the FFS method was fabricated. First, a substrate with electrodes was prepared. The substrate was a glass substrate with a size of 30 mm x 35 mm and a thickness of 0.7 mm. An IZO electrode was formed on the entire surface of the substrate as the first layer, which constituted the counter electrode. A SiN (silicon nitride) film formed by CVD was formed as the second layer on the first layer of the counter electrode. The thickness of the second layer of the SiN film was 500 nm, and it functions as an interlayer insulating film. A comb-shaped pixel electrode formed by patterning the IZO film was arranged as the third layer on the second layer of the SiN film, and two pixels, the first pixel and the second pixel, were formed. The size of each pixel was 10 mm in length and about 5 mm in width. At this time, the first layer of the counter electrode and the third layer of the pixel electrode were electrically insulated by the action of the second layer of the SiN film. The pixel electrodes in the third layer have a comb-like shape formed by arranging multiple L-shaped electrode elements with a bent central portion, as in the diagrams in JP 2014-77845 A (Japanese Patent Publication). The width of each electrode element in the short direction is 3 μm, and the distance between the electrode elements is 6 μm. Since the pixel electrodes forming each pixel are formed by arranging multiple L-shaped electrode elements with a bent central portion, each pixel is not rectangular in shape, but has a bold L-shaped shape that is bent at the center like the electrode elements. Each pixel is divided into upper and lower parts with the central bend as a boundary, and has a first region above the bent part and a second region below the bent part. Comparing the first and second regions of each pixel, the directions of the electrode elements of the pixel electrodes that compose them are different. That is, when the direction of the line segment of the polarization plane of the polarized ultraviolet light described later projected onto the substrate is used as a reference, the electrode elements of the pixel electrodes in the first region of the pixel are formed to form an angle of +80° (clockwise), and the electrode elements of the pixel electrodes in the second region of the pixel are formed to form an angle of -80° (clockwise). That is, the first and second regions of each pixel are configured such that the directions of the rotational movement (in-plane switching) of the liquid crystal in the substrate plane induced by the application of a voltage between the pixel electrode and the counter electrode are opposite to each other.

[0140] Next, the liquid crystal alignment agent obtained in the synthesis example and the comparative synthesis example was filtered through a 1.0 μm filter, and then applied by spin coating to the above-prepared electrode-attached substrate. Then, it was dried for 120 seconds on a hot plate set at 80°C. Then, using an exposure device manufactured by Ushio Inc.: APL-L050121S1S-APW01, linearly polarized ultraviolet light was irradiated from the vertical direction to the substrate through a wavelength selection filter and a polarizing plate. At this time, the polarization plane direction was set so that the direction of the line segment obtained by projecting the polarization plane of the polarized ultraviolet light onto the substrate was inclined at 80° with respect to the third layer IZO comb electrode. Then, it was baked in an IR (infrared) type oven at 230°C for 30 minutes to obtain a substrate with a polyimide liquid crystal alignment film having a thickness of 100 nm that had been subjected to an alignment treatment. In addition, a glass substrate having a columnar spacer with a height of 4 μm and an ITO electrode formed on the back surface as an opposing substrate was also subjected to an alignment treatment in the same manner as above to obtain a substrate with a polyimide liquid crystal alignment film. These two substrates with liquid crystal alignment film were used as a set, and a sealant was printed on one substrate with a liquid crystal injection port remaining, and the other substrate was attached and pressed so that the liquid crystal alignment film faces each other and the direction of the line segment projected by the polarized plane of polarized ultraviolet light on the substrate was parallel. The sealant was then cured to prepare an empty cell with a cell gap of 4 μm. Liquid crystal MLC-3019 (positive liquid crystal manufactured by Merck) was injected into this empty cell by the reduced pressure injection method, and the injection port was sealed to obtain a liquid crystal cell of the FFS mode. The obtained liquid crystal cell was then heated at 120°C for 30 minutes and left overnight at 23°C before being used for evaluation of liquid crystal alignment.

[0141] <Evaluation of liquid crystal alignment> When this liquid crystal cell was used, the liquid crystal cell in which flow alignment was confirmed was defined as “bad,” and the liquid crystal cell in which flow alignment was not confirmed was defined as “good.” The results are shown in Table 1.

[0142] [Table 1]

[0143] As can be seen from the above results, in the adhesion evaluation, the liquid crystal alignment film obtained from the liquid crystal alignment agent using the diamine compounds WA-1 and WA-2 showed higher adhesion than the liquid crystal alignment film obtained from the liquid crystal alignment agent using the diamine compound A5. Specifically, this is shown in the comparison between Examples 1-2 and Comparative Example 1 shown in Table 1. Furthermore, in the film strength evaluation, it was found that the liquid crystal alignment film obtained from the liquid crystal alignment agent using the diamine compounds WA-1 and WA-2 exhibited higher film strength than the liquid crystal alignment film obtained from the liquid crystal alignment agent using the diamine compound A5. Specifically, this is shown in the comparison between Examples 1-2 and Comparative Example 1 shown in Table 1. It was also found that the liquid crystal alignment films obtained from the liquid crystal alignment agents using diamine compounds WA-1 and WA-2 exhibited liquid crystal alignment properties equivalent to those of the liquid crystal alignment film obtained from the liquid crystal alignment agent using diamine compound A5. From the above, it is possible to improve the seal adhesion and film strength while maintaining the liquid crystal alignment by using WA-1 and WA-2, which have a biphenyl skeleton and specific side chains. [Industrial Applicability]

[0144] The liquid crystal display element using the liquid crystal alignment film obtained from the liquid crystal alignment agent of the present invention can be suitably used as a liquid crystal display element. These elements are also useful in liquid crystal displays for display purposes, and further in light control windows and light shutters for controlling the transmission and blocking of light.

Claims

1. A diamine having a structure represented by the following formula (1): 【Chemistry 1】 A is an alkyl group having 1 to 3 carbon atoms, a benzyl group, a p-methoxybenzyl group, an acetyl group, a benzoyl group, a t-butyloxycarbonyl group, a 9-fluorenylmethoxycarbonyl group, or R 1 R 2 R 3 represents a Si group, R 1 , R 2 and R 3 each independently represents an alkyl group having 1 to 3 carbon atoms or a phenyl group.

2. A polymer obtained by using the diamine according to claim 1.

Citation Information

Patent Citations

  • Liquid crystal element and method for manufacturing the same

    JP2018054761A

  • Liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element

    WO2010074269A1

  • Liquid crystal aligning agent, liquid crystal alignment film and liquid crystal display element

    WO2015060366A1

  • Liquid crystal aligning agent, liquid crystal alignment film and liquid crystal display element using same

    WO2016063834A1